Knowledge and practice of blood transfusion among nursing students in UiTM Puncak Alam Campus / Noor Azlin Mohd Abdullah and Nor Amirah Ali Mohammad - Mohd Abdullah, Noor Azlin; Ali Mohammad, Nor Amirah (2019)
Blood transfusion was a procedure in which blood or blood components are transferred from one person to another person. Blood component including red cells, platelets, fresh frozen plasma and cryoprecipitate in which the therapy was often used in managing hematologic diseases. This study aimed to determine the knowledge and practice of blood transfusion among nursing students in UiTM Puncak Alam Campus. The study utilized a descriptive cross-sectional design approach, 157 nursing students were selected as the respondent of the study. A modified Routine Blood Transfusion Knowledge Questionnaire (RBTKQ) was used to collect information in seven sections consists of demographic details, issues relating to patient preparation, blood pack collection, pre-transfusion, post-transfusion initiation nursing activities, a complication related to blood transfusion and issues related to blood transfusion policies and procedure. The practice of blood transfusion questionnaires which were structured along a three-point Likert scale. Data were analysed with SPSS version 22. Results showed that nursing students have poor knowledge in blood transfusion but they have good practice in blood transfusion. On common error, the respondents sometimes forgot to practice to take vital sign, especially about measured baseline respiration throughout the transfusion process. This study concludes that nursing students have poor knowledge of blood transfusion but always good in practice.